1999
DOI: 10.1177/016555159902500407
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the impact of information and communication technologies in sub-Saharan Africa

Abstract: Information and communication technologies (ICT) have been in use for over three decades in different settings inAfrica, but the impact of ICT on users in the region is not well documented. This paper attempts to examine the impact of ICT in sub-Saharan Africa, based on a study using a grounded theory approach. It was aimed at understanding users within their ICT applications context. Four main aspects of the impact of ICT were identified: 'Actual impact', 'Potential impact', 'Constraints' and 'Actions centred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…The unimpressive picture of IT exploitation in the Nigerian public sector appears to follow the general pattern in sub-Saharan Africa, as observed by Adam and Wood in a recent article [22]. However, it is clear that Nigerian public agencies must devote a much greater attention to modern information processing systems than previously if they are not to constitute a serious impediment to national socio-economic growth and development in the third millennium.…”
Section: Resultsmentioning
confidence: 75%
“…The unimpressive picture of IT exploitation in the Nigerian public sector appears to follow the general pattern in sub-Saharan Africa, as observed by Adam and Wood in a recent article [22]. However, it is clear that Nigerian public agencies must devote a much greater attention to modern information processing systems than previously if they are not to constitute a serious impediment to national socio-economic growth and development in the third millennium.…”
Section: Resultsmentioning
confidence: 75%
“…lack of private sector involvement (i.e. ICT manufacturers and operators) in designing ICTs suitable for poor countries (Adam and Wood, 1999;APF, 2008); 48 CWIS 31,1 . lack of human resource capacity which limits the ICT implementation (Adam and Wood, 1999;Raji et al, 2006;Farrell et al, 2007);…”
Section: Solar Electricity Generationmentioning
confidence: 99%
“…The study also outlines the structural and functional difficulties that need to be resolved around the area of using computers in education for nurses and midwifes. Adam and Wood (2006), in their study of the utilization of ICTs in African libraries, established among other factors the problem of lack of IL to determine the level of integration of IL within its academic programs. It was revealed that most of the students were ill-equipped with the requisite IL skills such as ability to find, identify, locate, review, select, and apply information needed for their studies and in the work environment; they had difficulties in using the relevant tools to locate information and knowledge; and had difficulties in critically evaluating, analyzing, and examining the information coming their way.…”
Section: Literature Reviewmentioning
confidence: 99%